Biomarkers for intracellular pathogens: establishing tools as vaccine and therapeutic endpoints for visceral leishmaniasis. (18th November 2013) - Vallur, A. C.; Duthie, M. S.; Reinhart, C.; Tutterrow, Y.; Hamano, S.; Bhaskar, K. R. H.; Coler, R. N.; Mondal, D.; Reed, S. G.; Bottieau, E.
Abstract Visceral leishmaniasis in South Asia is a serious disease affecting children and adults. Acute visceral leishmaniasis develops in only a fraction of those infected individuals, the majority being asymptomatic with the potential to transmit infection and develop disease. We followed 56 individuals characterized as being asymptomatic by seropositivity with rk39 rapid diagnostic test in a hyperendemic district of Bangladesh to define the utility of Leishmania‐specific antibodies and DNA in identifying infection. At baseline, 54 of the individuals were seropositive with one or more quantitative antibody assays and antibody levels persisted at follow up. Most seropositive individuals (47/54) tested positive by quantitative PCR at baseline, but only 16 tested positive at follow up. The discrepancies among the different tests may shed light on the dynamics of asymptomatic infections of Leishmania donovani, as well as underscore the need for standard diagnostic tools for active surveillance as well as assessing the effectiveness of prophylactic and therapeutic interventions.